2019
DOI: 10.1080/1828051x.2018.1549514
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of quebracho and chestnut tannins mix in rabbit: effects on live performances, digestibility, carcase traits, antioxidant status, faecal microbial load and economic value

Abstract: The effects of dietary supplementation of tannins mix (quebracho and chestnut) in rabbit diet were evaluated for productive performances, health parameters and digestibility in order to quantify their practical utilisation in the rearing system. One-hundred and twenty Martini group hybrid rabbits of 30 days old were fed four different diets for 60 days. The diets were formulated as: basal diet (negative control, C), basal diet supplemented by 0.3% of tannins mix (T0.3), basal diet supplemented by 0.6% of tanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…These findings are similar to those reported by Fathi et al (2019), who found that eucalyptus leaves did not affect dressing and fore or hind parts of the rabbit carcass. Similar results were found in slaughter traits of rabbits fed diet supplemented with ginger powder (Mancini et al, 2018), quebracho and chestnut (Mancini et al, 2019), or garlic and turmeric powder (Alagawany et al, 2016) as growth promoters.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are similar to those reported by Fathi et al (2019), who found that eucalyptus leaves did not affect dressing and fore or hind parts of the rabbit carcass. Similar results were found in slaughter traits of rabbits fed diet supplemented with ginger powder (Mancini et al, 2018), quebracho and chestnut (Mancini et al, 2019), or garlic and turmeric powder (Alagawany et al, 2016) as growth promoters.…”
Section: Discussionsupporting
confidence: 81%
“…Hinojosa Dávalos et al (2013) reported that Tithonia tubaeformis contains antioxidant compounds such as phenols and flavonoids. Some studies reported that pH was not affected by diets supplemented with ginger powder (Mancini et al, 2018), quercetin (North et al, 2018, Amarantus dubius (Molina et al, 2018), and quebracho and chestnut tannin mix (Mancini et al, 2019). However, Cullere et al (2016) added Silybum marianum to rabbit feed and found an increase in pH values, which is supposedly linked to glycolytic metabolism in the muscle intermediated by silibinin presence in Silybum marianum.…”
Section: Discussionmentioning
confidence: 99%
“…According to [ 83 ], rabbits fed diets with 4% of tanniniferous browsers of Acacia karroo, Acacia nilotica and Acacia tortilis showed no significant differences in intake and digestibility. Mancini et al [ 84 ] also reported no significant difference in growth rate, feed intake or feed conversion ratio and carcass traits of rabbits fed a mixture of quebracho and chestnut tannins. Moreover, [ 85 ] observed no significant difference in growth rate, feed intake or feed conversion ratio of rabbits fed low-tannin sorghum grains.…”
Section: Influence Of Tannins On the Productivity Of Monogastric Amentioning
confidence: 99%
“…There is a large variation in the chemical composition of the Eucalyptus species. The highest percentages of essential oils in the leaves of Eucalyptus are 1,8- 63]. Many studies have shown that eucalyptus oil and leaves can be used to improve productive, immunological, and physiological traits in humans [64,65], poultry [59,66,67], and ruminants [68].…”
Section: Eucalyptusmentioning
confidence: 99%